On Transmission of Multiresolution Gaussian Sources over Noisy Relay Networks - Ho, J.; Pin-Han Ho (IEEE transactions on wireless communications, 2013)
This paper investigates joint source-channel coding (JSCC) in a decode-and-forward three-node relay network, in which scalable source coding (SSC) is coupled with superposition coding (SPC) to form a layered coding architecture of SSC-SPC. In contrast to any previously reported research using asymptotic capacity-based distortion (CBD) measure, we derive the mean-squared error end-to-end distortion (EED) of such JSCC system based on a real-valued Gaussian source, aiming to achieve better precision and practicality for applications in which channels are subject to large error probabilities. The EED evaluation is formulated and applied to demonstrate achievable gains of the SSC-SPC architecture versus a number of conventional approaches. Power allocation optimization is performed based on the developed non-asymptotic EED model and compared to that by using an asymptotic CBD measure in which symbol losses caused by channel error cannot be considered. We demonstrate the performance gaps between results solved from EED versus CBD in our numerical example, and conclude that the optimization using CBD behaves awkwardly in computing proper power allocation configurations in the considered SSC-SPC architecture.